Administrative Arbitration and its effect on settlement of Administrative Contract Disputes. - - Assistant teacher Zaid Ajami Bashit; assistant teacher Rafid Ali Lafta (The college of law and political science journal, 2023)
f methods modern the of one is arbitration Administrative an plays and ,contracts administrative of field the in disputes resolving been has arbitration administrative of method The .this in role important by characterized are disputes contract Most .privacy by characterized of one is method arbitration the ,therefore ,qualities technical precise also Arbitration nature judicial the from it distinguishes that qualities good peacefully resolved is dispute the If.judiciary the on burden the reduces would that steps many summarizes this ,arbitrators administrative through of benefit the ,Thus .moment a for even ,judiciary the of work the disrupt administrative the from away moving by conflict the to parties the of each the reduce to is hand other the on State the and abhorrent methods which ,arbitration of method another is there and ,judiciary the on burden some in applied was which ,)arbitration administrative compulsory (ithat requires case The this in rule legislative a on based systems legal to resorting before tribunal arbitral the to resort dispute the to parties the important most the study this in reached have we and ,authorities judicial relating disputes the that is them among ,recommendations and findings ,methods technical and professionalism need contracts administrative to a with application N method flexible a as method arbitration the fit which effectiveness the support to study this in recommended as data renewed lead as role s›judiciary the grandiloquence of lack the and ,arbitration of so ,fails arbitration resulting one that in counterproductive and negative to of confluence the of delimitation the on controls the determine must you .judiciary arbitration th